Properties of manganite/ruthenate superlattices with ultrathin layers. Issue 4 (6th March 2013) - Ziese, Michael; Vrejoiu, Ionela
Abstract The properties of manganite/ruthenate superlattices are reviewed with a specific focus on the manganite/ruthenate interface. La0.7Sr0.3MnO3/SrRuO3 and Pr0.7Ca0.3MnO3/SrRuO3 superlattices grow with a high crystalline perfection as illustrated in the figure to the right: at the interface the individual cation species can be clearly identified, interdiffusion is marginal. The superlattices show magnetization processes with an intricate interplay between magnetocrystalline anisotropy, size of the layer magnetization, spin confinement and interfacial antiferromagnetic interlayer coupling. There is further an unprecedented Curie temperature stabilization at room temperature values of the La0.7Sr0.3MnO3 layers in the superlattices down to layer thicknesses of one unit cell. The magnetotransport properties, especially the Hall effect, indicate the existence of a quasi‐two‐dimensional hole gas at the La0.7Sr0.3MnO3/SrRuO3 interface; this is further supported by an analysis of cation displacements as determined from scanning transmission electron microscopy. The manganite/ruthenate interface might be considered as a model system for the study of interfacial reconstruction and charge transfer in a highly correlated ferromagnetic system. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> HAADF‐STEM micrograph of two La0.7Sr0.3MnO3/SrRuO3 interfaces in a superlattice with four unit cell thick La0.7Sr0.3MnO3 and eight unit cell thick SrRuO3 layers. The spheres indicate the cations as determined from the Z‐contrast. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)